Problem doboru ekspertów w procesie pozyskiwania wiedzy - Chmist, Stanisław (Selection of Experts in the Process of Knowledge Acquisition, 2006)
The identification of sources of knowledge is a very important stage in the process of knowledge acquisition. Experts relying on their own implicit knowledge are a very important source of knowledge. A correct selection of experts is not an easy task. This article contains some reflections on the level of expert knowledge and methods and criteria for the evaluation of the experts' level of knowledge.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 36-43